The Judges’ View at Mojokerto Religious Court on Polygamous Marriage’s Averment Perspective of Al-Ghazali’s Maslahat - Fibali, Arini Alghina (Sakina: Journal of Family Studies, 2021)
Islam does not prohibit a husband to have more than 1 wife, according to the word of Allah An-Nisa verse 3. Certainly, doing polygamy must use the procedures and conditions mentioned in law of concerning Marriage. The submission of Averment of polygamous marriage was declared not accepted if you do with unregistered married way. This research aims to know the views of the Mojokerto Religious Court judges on the Averment of polygamous marriage. From their opinions we will see with the Perspective Of Al-Ghazali‟s Maslahat. The type of this research is empirical research with a qualitative approach, then analized with perspective of Al-Ghazali‟s Maslahat. This study's results are the averment of polygamous marriage in this court is declared not accepted accordance with Supreme Court Circular No. 3 of 2018. So in order for unregistered polygamous marriage be recognized by state, it must be remarried to protect material rights of wife. In contrast to child resulting, that is still protected by the Constitutional Court decision No.46 of 2010. If the judges don‟t grant case Averment of polygamous marriage, this is when reviewed using Al-Ghazali‟s maslahat‟s theory. It‟s accordance with fiqh‟s rules because averment of polygamous marriage has more mafsadat than benefit.